Phylogenomics and chromosome mapping show that ectopic recombination of subtelomeres is critical for antigenic diversity and has a complex evolutionary history in Plasmodium parasites - Martínez-Eraso, Carolina; Cárdenas, Heiber; Cerón-Romero, Mario A. (Frontiers in Ecology and Evolution, 2024)
Antigenic diversity is critical for parasites to coevolve with their hosts. Plasmodium falciparum generates antigenic diversity through ectopic recombination of their antigenic gene-rich subtelomeres, a mechanism that takes place after chromosomal ends anchor close together in the nuclear membrane. A study mapping the phylogenomic history of genes across the chromosomes of P. falciparum showed that this mechanism to generate antigenic diversity extends to all chromosomes. Yet, its existence, importance, and evolutionary history in other Plasmodium species remain largely unknown. In this study, we survey and compare genomic features associated with the mechanism to generate antigenic diversity by ectopic recombination of subtelomeres in 19 species widely distributed in the genus Plasmodium. By comparing these features across species using a phylogenomic framework, we assess the existence and intensity of this mechanism, as well as propose different hypotheses for its evolution. Our results suggest that ectopic recombination of subtelomeres is more critical for the diversification of pir or rif/stevor genes than other antigenic gene families. Furthermore, its intensity varies among subgenera and was likely acquired and lost multiple times in the phylogeny of Plasmodium. These results demonstrate, for the first time, the genomic and evolutionary complexity of this mechanism for generating antigenic diversity in the genus Plasmodium.